Institutional Injustice: How Public Administration Has Fostered and Can Ameliorate Racial Disparities. Issue 2 (February 2021) - House-Niamke, Stephanie; Eckerd, Adam
In a culture with institutionalized racial disparities, administrative norms that attempt to ensure rational decisions through the use of aggregation and quantification can exacerbate the racial disparities that policy attempts to address. We argue that it will be difficult for policy to address the problem without a fundamental reorientation of the ways that administrators make decisions based on race. We conclude by offering some suggestions for how this reorientation can begin.